Novel brain SPECT imaging unravels abnormal cerebral perfusion in patients with postural orthostatic tachycardia syndrome and cognitive dysfunction - Marie-Claire Seeley; Howard O’Brien; Gemma Wilson; Clair Coat; Tess Smith; Kevin Hickson; Reynold Casse; Amanda J. Page; Celine Gallagher; Dennis H. Lau (Scientific Reports)
Abstract Cognitive dysfunction is frequently reported in individuals with postural orthostatic tachycardia syndrome (POTS), possibly resulting from reduced cerebral blood flow (CBF). We used brain SPECT, an accessible imaging modality that has not been systematically evaluated in this patient group. Retrospective review of participants from our registry was undertaken to identify those who had a brain SPECT performed for investigation of cognitive dysfunction. Abnormal CBF was taken as z-score > 2 standard deviations of healthy control reference values. Patient reported outcome measures (PROMs) such as autonomic, gastric and quality of life symptom scores were analyzed. From a total of 56 participants (mean 34.8 ± 10.7 years, 88% females), PROMs indicate: moderate to severe autonomic dysfunction in 75%; at least mild to moderate gastroparesis in 23%; low global health rating and utility scores. Abnormal CBF was seen in 61% but did not differ by POTS triggers. The regions with the lowest mean z-scores were the lateral prefrontal and sensorimotor cortices. Hierarchal regression analyses found number of brain regions with abnormal CBF, autonomic and gastric symptoms to account for 51% of variances in health utility. Cerebral hypoperfusion is prevalent in those with POTS and cognitive dysfunction even whilst supine, contributing to reduced quality of life.